Precocious ischemia preceding bilateral adrenal hemorrhage: A case report - Galatola, Roberta (Radiol Case Rep, 2020)
We present a case of a middle-age male who presented in emergency room with nonspecific abdominal pain. A contrast-enhanced computer tomography (ceCT) scan showed a reduced perfusion of both adrenal glands. The clinical examinations and the laboratory tests were negative for an adrenal pathological process. To reassess the adrenal ischemia, a second ceCT scan was performed 5 days later showing an acute bilateral adrenal hemorrhage. These findings demonstrated that the previous adrenal hypoperfusion represented the prodromal manifestation of a hemorrhagic intraglandular process. This case suggests that adrenal hypoperfusion detected on tomographic imaging dictates a prompt clinical management finalized to strictly monitor the potential evolution towards a more aggressive pathological condition and confirms the pivotal role of imaging in the diagnosis of such uncommon disorder.